Dust Entrainment in Photoevaporative Winds: Synthetic Observations of Transition Disks - Perez-Marquez, S (EDP Sciences, 2022)
Context. X-ray- and extreme-ultraviolet- (XEUV-) driven photoevaporative winds acting on protoplanetary disks around young T Tauri stars may strongly impact disk evolution, affecting both gas and dust distributions. Small dust grains in the disk are entrained in the outflow and may produce a detectable signal. In this work, we investigate the possibility of detecting dusty outflows from transition disks with an inner cavity. Aims. We compute dust densities for the wind regions of XEUV-irradiated transition disks and determine whether they can be observed at wavelengths 0.7 âÃ Â‰ ² λobs [μm] âÃ Â‰ ² 1.8 with current instrumentation. Methods. We simulated dust trajectories on top of 2D hydrodynamical gas models of two transition disks with inner holes of 20 and 30 AU, irradiated by both X-ray and EUV spectra from a central T Tauri star. The trajectories and two different settling prescriptions for the dust distribution in the underlying disk were used to calculate wind density maps for individual grain sizes. Finally, the resulting dust densities were converted to synthetic observations in scattered and polarised light. Results. For an XEUV-driven outflow around a M∗ = 0.7 M· T Tauri star with LX = 2 Ã - 1030 erg s-1, we find dust mass-loss rates 1dust â 2; 2.0 - 103gas, and if we invoke vertical settling, the outflow is quite collimated. The synthesised images exhibit a distinct chimney-like structure. The relative intensity of the chimneys is low, but their detection may still be feasible with current instrumentation under optimal conditions. Conclusions. Our results motivate observational campaigns aimed at the detection of dusty photoevaporative winds in transition disks using JWST NIRCam and SPHERE IRDIS. ©